Seções finais em artigos acadêmicos da estatística: uma análise crítica de gênero - Yamin, Sofia Uberti (2019)
In Brazil, disciplinary areas such as Chemistry, Engineering and Statistics predominantly publish in English, which implies the need for knowledge about formal and functional conventions required by the social and discursive practices typical of each area. Although research article (RA) has been extensively investigated for teaching purposes in recent decades (SWALES 1990; 2004; MOTTA-ROTH; HENDGES 2010), there is still a need to investigate scientific discourse and academic writing in specific disciplinary areas. In addition, there is a lack of research on the Results and Discussion sections of the experimental research article, since researchers publish to report scientific results and acquire recognition in the field. This study aims to investigate and describe elements of rhetorical organization and features of the discourse in the Results and Discussion / Conclusion sections of the experimental research article of Statistics. For this purpose, this study is based on the theoreticalmethodological perspective of the Critical Genre Analysis (Motta-Roth 2008, Motta-Roth; Heberle 2015), which provides theoretical and methodological tools for textual and contextual analysis. In this study, two representative journals in Statistics and 40 RAs published in English were analyzed in light of the relevant literature and through consultations with an informant from the UFSM Statistics undergraduate program. Textual analysis results reveal that the RA in Statistics does not present the typical organization of experimental papers - IMRD (Swales 1990). After the Introduction section, the information regarding background, methodology and results are presented in different sections with varied titles, which present a recurrent sequence. Results are present in two sections named Simulation Studies and Applications, which start with methodological information. And finally, the Discussion / Conclusion section presents defined titles. The rhetorical organization of the results sections presents a significant emphasis on the movements of procedures and description of the simulation and application scenario since, according to information obtained from informants, the methodology and presentation of statistical models play a very important role in publications in the area's RA. The discussion section, which is sometimes referred to as the conclusion, presents a rhetorical organization similar to that from previous research (Hopkins, Dudley-Evans, 1988, Yang and Allison, 2003). We hope this study can contribute to increase the awareness about the process of reading and writing, contributing to the development of EAP teaching materials, both in this investigated discipline (for the EAP course in Statistics degree at UFSM), and in other disciplinary areas.